Global need for climate advocacy, education and evidence in paediatrics - Tony Waterston; Dhurgshaarna Shanmugavadivel; Alison Leaf; Alison Firth; Haytham Ali; Rebecca Rhodes; Cinthu Vivehananthan; Ekundayo Ajayi-Obe; Georgia Bickerton; Praveen Sreekanthalal; Bernadette Anne-Marie O’Hare; Nancy Abdel Salam Ahmed Gomaa; et al. (BMJ Paediatrics Open)
Climate change is the single greatest existential threat to children worldwide, adversely affecting the health and well-being of children and young people.The Royal College of Paediatrics and Child Health members living outside the UK (respondents) were invited to an online anonymised survey where opting-in participants answered 32 questions covering 6 domains.139 respondents from 50 countries responded to the survey. Respondents agreed that climate change influences the rising rates of children with heat-related (50%), infectious (64%) and mental health (36%).The climate crisis is a global emergency, and working together is paramount to safeguarding the planet for future generations.